An optimized microchamber method for rapid screening of rice for sheath blight resistance in the Philippines (The Philippine Journal of Crop Science, 2012)
Breeding resistance to sheath blight (caused by Rhizoctonia solani Kuhn) in rice is constrained by the lack of highly resistant donors and a rapid, simple but effective screening method. The use of microchambers such as plastic soda bottles provides better control of humidity and temperature necessary for growth and establishment of the causal organism. In this study, the microchamber protocol was optimized for rapid and effective screening. The factors considered are: 1) kind of inoculum carrier, 2)seedling age for inoculation, 3) length of incubation periodprior to disease evaluation, 4) disease scoring system. Results indicate that R. solani grows better using mycelial disks as inoculum carrier as compared to rice hull substrate. Seedlings can be inoculated as early as 14 d after sowing and disease scoring can be done at 5-7 d after inoculation. Using the standard evaluation system for rice (IRR 2002) as basis, a modified scoring system that takes into account seedling age during inoculation and use of qualitative and quantitative disease indices was also developed. Using these optimized parameters, screening results can be obtained in less than a month after seed germination. In subsequent experiment, 103 breeding lines matched with the previous results of induced field screening. Moreover, the resistant to moderately resistant reactions reported for 10 rice accessions were also confirmed using the microchamber method. The optimized microchamber method is fast, simple, reliable and economical compared to the traditional method of screening for sheath blight resistance.